Mean Platelet Volume, Association with Inflammatory and Nutritional Markers in Maintenance Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2021)
Introduction. Mean Platelet Volume (MPV) has been revealed to be a risk factor for ischemic heart disease in the hemodialysis patients .The aim of present study is to investigate the association between MPV level with inflammatory and nutritional factors in patients requiring chronic hemodialysis. Methods. 100 patients who were on maintenance hemodialysis were included. Based on the median MPV (8.7 fL) patients were divided into two groups of low and high MPV level to assess and compare in terms of inflammatory (erythrocyte sedimentation rate, C-reactive protein, and transferrin), and nutritional (albumin, ferritin, uric acid, blood urea nitrogen, creatinine, triglyceride, cholesterol, low density lipoprotein, and high density lipoprotein) parameters. Results. The median MPV level in our patients was 8.7 ± 1.8 fl. There was no statistical difference in the level of inflammatory and nutritional markers between the two groups, and none of them were related to MPV level (P > .05). The prevalence of IHD was significantly higher in the high MPV group (P < .05). After adjustment for the age, no association was observed between different parameters and MPV level except for transferrin in patient’s ≤ 60 years old. Mean transferrin levels were significantly lower in the high MPV group (P < .05). Conclusion. Present study did not show any association between inflammatory and nutritional markers with MPV level in hemodialysis patients except for the transferrin level in younger cases.